Payoff implications of incentive contracting. Issue 4 (11th November 2021) - Garrett, Daniel F.
Abstract : In the context of a canonical agency model, we study the payoff implications of introducing optimally structured incentives. We do so from the perspective of an analyst who does not know the agent's preferences for responding to incentives, but does know that the principal knows them. We provide, in particular, tight bounds on the principal's expected benefit from optimal incentive contracting across feasible values of the agent's expected rents. We thus show how economically relevant predictions can be made robustly given ignorance of a key primitive.